The Reaching Agents of Change (RAC) Project in Tanzania (2011-2014) - International Potato Center (2014)
RAC has strengthened the capacity of Sokoine University of Agriculture (SUA) as well as that of 15 national facilitators to conduct training of trainers (ToT) courses on sweetpotato. A total of 76 secondary trainers and 2,899 tertiary trainers and farmers have been trained.